Chest Pain and Exercise Induced Ischemia with Angiographically Insignificant Coronary Arterial Disease: Clinical Presentation and Follow-Up (University Heart Journal, 2011)
Angiography of patients with typical chest pain reveals normal epicardial coronary arteries in about 15-20%. ECG changes suggestive of myocardial ischemia during exercise also can be demonstrated in this subset of the patients. Total 58 patients (42 females) with mean age 42±7 years who were undergoing coronary angiogram in the Department of Cardiology, University Cardiac Center, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2005 to December 2009 were evaluated. The patients were recruited on the basis of presence of history of chest pain, with normal resting ECG and ischemia like ECG changes during exercise stress test. 32.8% patients had hypertension and 15.5% were diabetics, 19.0% had dyslipidemia and 6.9% had family history of ischemic heart disease. All the patients were having positive exercise stress test. Angiographic findings showed luminal irregularities in 29.3% patients, 15.5% patients had luminal stenosis less than 30% and rest had normal coronary angiogram. Follow up of the patients after one and six months of angiogram was done. After one month 63.8% patients remained symptomatic and after six months 63.3% patients remained symptomatic despite maximum medical management. The pathophysiology and appropriate management of this subset of the patients still remained a challenge for physicians. Optimum management of cardiovascular risk factors is very important issue in this group of patients.Key words: Angiography; Epicardial coronary arteries; Exercise stress test; Cardiovascular risk factors. DOI: 10.3329/uhj.v6i1.7187University Heart Journal Vol.6(1) 2010 pp.27-31